2010
DOI: 10.1016/j.immuni.2009.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Melanization Pathways in the Mosquito Aedes aegypti

Abstract: Serine protease cascades are involved in blood coagulation and immunity. In arthropods, they regulate melanization, which plays an important role in immune defense and wound healing. However, the mechanisms underlying melanization pathways are not completely characterized. We found that in the mosquito Aedes aegypti, there are two distinct melanization activation pathways carried out by different modules of serine proteases and their specific inhibitors serpins. Immune melanization proteases (IMP-1 and IMP-2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
137
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(142 citation statements)
references
References 48 publications
(81 reference statements)
5
137
0
Order By: Relevance
“…1 ). The significance of this immune defense in limiting infections caused by pathogenic organisms has been emphasized during the last few years [9,17,18] .…”
Section: Introductionmentioning
confidence: 99%
“…1 ). The significance of this immune defense in limiting infections caused by pathogenic organisms has been emphasized during the last few years [9,17,18] .…”
Section: Introductionmentioning
confidence: 99%
“…Other biochemical studies have identified serpins, which inhibit chymotrypsin-and subtilase-like serine proteases and papain-like cysteine proteinases (Oley et al, 2004;Osterwalder et al, 2004;Richer et al, 2004), and suggested that Drosophila Spn42Da isoforms may be essential for immune defense by inhibiting pathogenic proteolytic enzymes (Brüning et al, 2007). Additionally, insect serpins have been reported to be involved in regulation of the Toll pathway and prophenoloxidase activation (Tong et al, 2005;Shin et al, 2006;An and Kanost, 2010;Zou et al, 2010;An et al, 2011;Chu et al, 2015;Liu et al, 2015). In our previous work, a bee (Apis cerana) serine protease inhibitor exhibited inhibitory activities against subtilisin A and proteinase K (Kim et al, 2013b) and a bumblebee (Bombus ignitus) serine protease inhibitor inhibited chymotrypsin, subtilisin A, and proteinase K (Wan et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In Bombyx mori, serpin-15 inhibited prophenoloxidase activation and the expression of antimicrobial peptides . In Aedes aegypti, Anopheles gambiae, and Manduca sexta, serpins have also been reported to be involved in the regulation of the Toll pathway and prophenoloxidase activation (Tong et al, 2005;Shin et al, 2006;An and Kanost, 2010;Zou et al, 2010;An et al, 2011;Chu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The circulating microfilariae have short life cycle in human blood circulation; a proportion of the microfilariae can be removed by anti-microfilarial antibody www.intechopen.com (Simonsen et al, 1996;Ravindran et al, 2003). They develop two molts (L1 and L2) and induce the infection in susceptible mosquito vectors while the infected mosquitoes can regulate melanization involved in innate immune defense and wound healing to the penetration of filarial nematodes (Zou et al, 2010;Castillo et al, 2011). In blood-engorged mosquitoes that harbor high microfilarial density, they can induce death due to the vector intolerance against development of juvenile forms, and consequently, this leads to loss of L3.…”
Section: Factors That Favor Eliminationmentioning
confidence: 99%